Kinetoplast as a Potential Chemotherapeutic Target of Trypanosomatids - Machado Motta, Maria C. (Current Pharmaceutical Design, 2008)
Many trypanosomatid protozoa, such as those belonging to the Trypanosoma and Leishmania genera cause serious diseases to man. Such parasites present an unusual feature, a mitochondrial DNA arranged in catenated circles, known as kinetoplast DNA (kDNA). The replication of kDNA network is a complex process, which involves many proteins. Some of them are classified as topoisomerases and play essential biological roles, not only on kDNA synthesis, but also in the dynamics of the network topology, constituting the main target for drugs in kinetoplast. DNA binding drugs are also reported as chemotherapeutic agents against trypanosomatid infections. This review summarizes what is known about kinetoplast as a potential chemotherapeutic target for trypanosomatid protozoa.
Keywords: kinetoplast